2011
DOI: 10.1007/s13204-011-0026-z
|View full text |Cite
|
Sign up to set email alerts
|

Quick single-step mechanosynthesis of ZnO nanorods and their optical characterization: milling time dependence

Abstract: We report on the growth of ZnO nanorods (NRs) by a quick single-step mechanochemical process and investigated the milling time dependence on the structural and optical properties of the ZnO NRs. Mechanochemical reactions are carried out in a planetary ball mill for the time durations ranging from 30 min to 5 h. XRD and TEM studies revealed wurtzite structure of the as-grown ZnO NRs with length of several hundreds of nanometers to few micrometers after 30 min of reaction. Average diameter of the as-grown ZnO NR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…The results revealed no significant effect on the shape or particle size of nano ZnO. Regarding the grinding time's effect; the present results are in contrast to results obtained by Dhara and Giri [73] and Salah et al [74] that revealed the decrease in the particle size by increasing the milling reaction time. Elucidation of this contrast can be based on one of the two following assumptions; the first assumption is that long-time grinding produces smaller particles with higher surface areas, the high surfaced particles tend to agglomerate producing larger ones [75] due to Van der Waals or other attractive forces.…”
Section: Fig 2 Xrd Of Samples (G) (F) and (H)contrasting
confidence: 95%
“…The results revealed no significant effect on the shape or particle size of nano ZnO. Regarding the grinding time's effect; the present results are in contrast to results obtained by Dhara and Giri [73] and Salah et al [74] that revealed the decrease in the particle size by increasing the milling reaction time. Elucidation of this contrast can be based on one of the two following assumptions; the first assumption is that long-time grinding produces smaller particles with higher surface areas, the high surfaced particles tend to agglomerate producing larger ones [75] due to Van der Waals or other attractive forces.…”
Section: Fig 2 Xrd Of Samples (G) (F) and (H)contrasting
confidence: 95%
“…The peak at 377 nm originates from excitonic absorption [38]. This ZnO peak is much stronger in the presence of gold clusters, which is attributed to a possible enhancement of the ZnO UV peak caused by plasmonic local field enhancement [21].…”
Section: Resultsmentioning
confidence: 97%
“…We have synthesized ZnO NRs of various diameters by mechanosynthesis method at room temperature for reaction time as short as 30 minutes (Chakraborty et al, 2011;Dhara & Giri, 2011b). For the growth of ZnO NRs, mechanochemical reactions were carried out in a planetary ball-milling apparatus.…”
Section: Mechanosynthesis Methodsmentioning
confidence: 99%